OVERCOMING THE PROBLEMS OG HEUVEL TRIBE OFFLINE STORE BASED ON 4P MARKETING AND IMPLEMENTING THE TEACHINGS OF TAMANSISWA - Legiman; Ratnasari, Ayu; Fatoni, Rizal; of Ramadan, Star; Amandasari, Adellia; Kencana Dewi, Nawang; Dwi Cahya, Agus; Siripipatthanakul, Supaprawat (EMPOWERING HUMANITY, 2024)
This community service program aims to apply the values taught by Ki Hadjar Dewantara Ngandel (trust), Kendel (courage), Bandel (perseverance), and Kandel (resilience) to improve the performance of the "Heuvel Tribe" clothing store, which has been experiencing a decline in sales at its physical location. The program took place from October 3-21, 2024, involving six participants who were enthusiastically engaged in each session. The materials provided were specifically designed to help address the challenges faced by the Heuvel Tribe. Collaboration with the store facilitated the delivery of solutions and strategies to increase sales, which were well received by store management. As a token of appreciation, Heuvel Tribe received a certificate recognizing their contribution to this community service program. Participants hope that this program can continue sustainably to support the growth of local businesses.